Randomized clinical trial of open versus laparoscopic left lateral hepatic sectionectomy within an enhanced recovery after surgery programme (ORANGE II study). Issue 5 (31st January 2017) - Wong-Lun-Hing, E M; van Dam, R M; van Breukelen, G J P; Tanis, P J; Ratti, F; van Hillegersberg, R; Slooter, G D; de Wilt, J H W; Liem, M S L; de Boer, M T; Klaase, J M; Neumann, U P; et al.
Abstract: Background: Laparoscopic left lateral sectionectomy (LLLS) has been associated with shorter hospital stay and reduced overall morbidity compared with open left lateral sectionectomy (OLLS). Strong evidence has not, however, been provided. Methods: In this multicentre double-blind RCT, patients (aged 18–80 years with a BMI of 18–35 kg/m 2 and ASA fitness grade of III or below) requiring left lateral sectionectomy (LLS) were assigned randomly to OLLS or LLLS within an enhanced recovery after surgery (ERAS) programme. All randomized patients, ward physicians and nurses were blinded to the procedure undertaken. A parallel prospective registry (open non-randomized (ONR) versus laparoscopic non-randomized (LNR)) was used to monitor patients who were not enrolled for randomization because of doctor or patient preference. The primary endpoint was time to functional recovery. Secondary endpoints were length of hospital stay (LOS), readmission rate, overall morbidity, composite endpoint of liver surgery-specific morbidity, mortality, and reasons for delay in discharge after functional recovery. Results: Between January 2010 and July 2014, patients were recruited at ten centres. Of these, 24 patients were randomized at eight centres, and 67 patients from eight centres were included in the prospective registry. Owing to slow accrual, the trial was stopped on the advice of an independent Data and Safety Monitoring Board in the Netherlands. No significant difference in median (i.q.r.) time to functional recovery was observed between laparoscopic and open surgery in the randomized or non-randomized groups: 3 (3–5) days for OLLS versus 3 (3–3) days for LLLS; and 3 (3–3) days for ONR versus 3 (3–4) days for LNR. There were no significant differences with regard to LOS, morbidity, reoperation, readmission and mortality rates. Conclusion: This RCT comparing open and laparoscopic LLS in an ERAS setting was not able to reach a conclusion on time to functional recovery, because it was stopped prematurely owing to slow accrual. Registration number: NCT00874224 (https://www.clinicaltrials.gov ). Abstract : A lesson in trial design